The development and implementation of a layperson trauma first responder course in La Paz, Bolivia: A pilot study. Issue 5 (May 2018) - Boeck, Marissa A.; Callese, Tyler E.; Nelson, Sarah K.; Schuetz, Steven J.; Fuentes Bazan, Christian; Saavedra Laguna, Juan Mauricio P.; Shapiro, Michael B.; Issa, Nabil M.; Swaroop, Mamta
Abstract: Background: Ninety percent of nearly five million annual global injury deaths occur in low- and middle-income countries (LMICs), where prehospital care systems are frequently rudimentary or nonexistent. The World Health Organization considers layperson first-responders as essential for emergency medical services in low-resource settings lacking more formalized systems. This study sought to develop and implement a layperson trauma first responder course (TFRC) in Bolivia. Materials and methods: In March and April 2013 nine sessions of the eight-hour TFRC were held in La Paz, Bolivia. The course charged a nominal fee, and was led by an American surgeon and medical student. The TFRC built upon existing models with local stakeholder input, and included both didactic and practical components. Participants completed a baseline survey, and pre and posttests. The primary outcome was test performance, with secondary outcomes including demographic sub-group test score analyses and exam question validation. Data were assessed using nonparametric and psychometric methods Results: One hundred fifty-nine individuals met study inclusion criteria. Participant median age was 28 (IQR 24, 36), 49.1% were male, 59.1% worked in a medical field, most had secondary (35.2%) or university (56.0%) level educations, and 67.3% had prior first aid training. Median test scores improved after course completion (48% vs. 76%, p < 0.001), along with skill confidence (4 vs. 4.5, p < 0.001). Most questions had appropriate item difficulty indices, point bi-serial correlation coefficients, and positive Pretest Posttest Difference Indices. Cronbach alpha coefficients for pre and posttest scores were 0.72 and 0.78, respectively. Conclusions: This study presents data from the first offering of an original TFRC for laypeople in Bolivia. Increased participant knowledge and skill confidence after course completion, and acceptable overall psychometric test properties, indicate this model is valid and effective. Future aims include TFRC revision, and enrollment of more layperson first responders to increase population-level impacts.